Stress-induced polyubiquitination of proteasomal ubiquitin receptors targets the proteolytic complex for autophagic degradation. Issue 4 (3rd April 2017) - Cohen-Kaplan, Victoria; Ciechanover, Aaron; Livneh, Ido
ABSTRACT: Ubiquitin (Ub) is a small protein (8 kDa) found in all eukaryotic cells, which is conjugated covalently to numerous proteins, tagging them for recognition by a downstream effector. One of the best characterized functions of Ub is targeting proteins for either selective degradation by the proteasome, or for bulk degradation by the autophagy-lysosome system. The executing arm of the UPS is the 26S proteasome, a large multicatalytic complex. While much is known about the synthesis and assembly of the proteasome's subunits, the mechanism(s) underlying its removal has remained obscure, similar to that of many other components of the ubiquitin-proteasome system. Our recent study identified autophagy as the degrading mechanism for the mammalian proteasome, mostly under stress conditions. Amino acid starvation induces specific ubiquitination of certain 19S proteasomal subunits that is essential for its binding to SQSTM1/p62, the protein that shuttles the ubiquitinated proteasome to the autophagic machinery. SQSTM1 delivers ubiquitinated substrates for proteasomal degradation via interaction of its PB1 domain with the 19S proteasomal subunit PSMD4/Rpn10, in situations where the proteasome serves as a "predator." In contrast, we found that the UBA domain of SQSTM1 is essential for its interaction with the ubiquitinated proteasome and its delivery to the autophagosome, rendering the proteasome a "prey."